High-light-transmittance double-silver LOW-E glass and preparation method thereof
By preparing and processing bamboo powder and lithium modified cellulose films, the problems of glass substrate damage and light transmittance decrease during the coating process of double silver LOW-E glass are solved, and the preparation of double silver LOW-E glass with high light transmittance and heat insulation effect is achieved.
Patent Information
- Application Number
- CN202510092597.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
AI Technical Summary
The existing double silver LOW-E glass is prone to damage to the glass substrate when coated with a multi-layer film, and the increase in the thickness of the coating will lead to a decrease in light transmittance.
The cast film liquid is prepared by preparing the treated bamboo powder and reacting NaOH solution and urea with DMAC to form a lithium-modified cellulose film, which enhances the mechanical strength and thermal stability of the glass substrate, and the multi-layer film is coated through a magnetron sputtering coating process.
The preparation of high-light transmittance double silver LOW-E glass is achieved, avoiding damage to the glass substrate during coating, and maintaining high transparency and thermal insulation effect.
Smart Images

Figure CN119912178A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass preparation, and in particular to a high-transmittance double-silver LOW-E glass and a preparation method thereof. Background Art
[0002] LOW-E glass, also known as low-emissivity glass, is a special coated glass that significantly reduces its emissivity by coating one or more layers of metal or metal oxide films on its surface. This glass can effectively block the transfer of infrared rays and heat while allowing visible light to pass through, so it is widely used in the construction and automotive industries. Double-silver LWO-E glass significantly improves its thermal insulation performance by coating two layers of silver and multiple layers of metal oxide or nitride films on its surface. Compared with single-silver glass and ordinary LOW-E glass, double-silver LOW-E glass has better performance in energy saving and optical performance.
[0003] The coating of double-silver LOW-E glass mainly consists of a first layer of metal oxide as a buffer layer, a second layer of silver for reflecting infrared rays, a third layer of nitride or metal oxide for protecting the silver layer, a fourth layer of silver for increasing reflectivity and heat insulation effects, and a top protective layer for providing durability and corrosion resistance. For a structure like this, the film layers can be replaced and increased or decreased according to different functions. The existing coating technology is generally through magnetron sputtering coating. When more waves need to be plated, the glass substrate is repeatedly plated under vacuum pressure, which can easily cause damage to the glass substrate. If the plated film layer requires better physical strength, the thickness of the film layer increases, and the transmittance will decrease. Therefore, the present invention provides a high-transmittance double-silver LOW-E glass and a preparation method thereof to solve the above problems. Summary of the invention
[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-transmittance double-silver LOW-E glass and a preparation method thereof.
[0005] A method for preparing high-transmittance double-silver LOW-E glass comprises the following steps:
[0006] S1: Preparation and processing of bamboo powder
[0007] The raw bamboo stalks are crushed and sieved, soaked in deionized water, heated, then allowed to stand and cool to room temperature, peroxyformic acid solution is added, and then concentrated sulfuric acid is added, followed by heating for 3-4 hours, centrifuged, filtered to remove the liquid, and dried to obtain treated bamboo powder;
[0008] S2: Preparation of casting solution
[0009] The treated bamboo powder is immersed in a NaOH solution, and the liquid is filtered out after heating and stirring, and the powder is washed with deionized water three times to obtain an alkalized bamboo powder, the alkalized bamboo powder, urea and DMAC are mixed, and the mixture is heated in an oil bath for reaction, and then the mixture is allowed to stand and cool to room temperature, the filtrate is filtered out, the filter residue is washed and dried to obtain an intermediate, the intermediate is added to a NaOH solution, and the mixture is taken out after cooling and stirring, and the mixture is heated, and the mixture is allowed to stand and degassed to obtain a casting solution;
[0010] S3: Treating the glass substrate
[0011] The casting liquid is evenly poured on the glass substrate and scraped flat with a scraper, and then the glass substrate is immersed in a dilute sulfuric acid solution, taken out after the phase separation process is completed, and rinsed with deionized water to obtain a glass substrate covered with a regenerated cellulose membrane, and the glass substrate with the regenerated cellulose membrane is immersed in a LiOH solution with the membrane-covered side facing downward, taken out and rinsed, and then dialyzed in a saturated LiCl solution, taken out and rinsed, and dried to obtain a glass substrate covered with a lithium-modified cellulose membrane;
[0012] S4: Preparation of high-transmittance double-silver LOW-E glass
[0013] A film is coated on a glass substrate covered with a lithium-modified cellulose film by a magnetron sputtering coating process, wherein the film layer materials are, from bottom to top, the second film layer Si3N4, with a film thickness of 15-20nm; the third film layer is ZnO, with a film thickness of 12-16nm; the fourth film layer is Ag, with a thickness of 5-8nm; the fifth film layer is Al2O3, with a film thickness of 20-25nm; the sixth film layer is a lithium-modified cellulose film, the coating method is the same as step S3, with a thickness of 20-30nm; the seventh film layer is Si3N4, with a film thickness of 15-20nm; the eighth film layer is ZnO, with a film thickness of 12-16nm; the ninth film layer is Ag, with a film thickness of 10-15nm; the tenth film layer is Al2O3, with a film thickness of 20-30nm; and the eleventh film layer is SnO2, with a thickness of 25-35nm, thereby obtaining high-transmittance double-silver LOW-E glass.
[0014] Furthermore, step S1 of preparing and processing bamboo powder comprises the following steps:
[0015] S1.1: Crush the raw bamboo stems and pass them through an 80-mesh sieve, soak them in deionized water at a solid-liquid ratio of 1 g: (10-15) mL, heat them to 80-90°C and soak them for 4-6 hours, then cool them to room temperature, add a peroxyformic acid solution, and add 10 g of peroxyformic acid per 1 g of crushed raw bamboo stems, and then add concentrated sulfuric acid at a total mass of 0.5% of the system;
[0016] S1.2: Then heat to 80-100°C, react for 3-4h, then centrifuge at 2000-2200r / min for 15-20min, remove the liquid by suction filtration, and dry at 60-65°C for 3-4h to obtain treated bamboo powder.
[0017] Furthermore, the peroxyformic acid solution is prepared by mixing 30% by mass of hydrogen peroxide and 85% by mass of formic acid in a volume ratio of (2-3):1.
[0018] Furthermore, step S2 of preparing a casting solution comprises the following steps:
[0019] S2.1: Soak the treated bamboo powder in a NaOH solution and heat it to 60-70°C. After stirring for 3-4 hours, filter and remove the liquid, wash with deionized water for 3 times to obtain alkalized bamboo powder, mix the alkalized bamboo powder, urea and DMAC in a volume ratio of 1:3:(2-4), heat to 80-90°C in an oil bath, and pass nitrogen at the same time, react for 1-2 hours, then stand and cool to room temperature, filter and remove the filtrate, then wash the filter residue with deionized water for 3 times, and dry it in an oven at 50-60°C for 4-5 hours to obtain an intermediate;
[0020] S2.2: Add the intermediate into NaOH solution, cool it to -20℃, and stir it at 60-80r / min for 3-4h. During the process, the reactants dissolve and gradually become transparent. During the cooling period, check the temperature of the reactants until the temperature reaches -20℃. After the reactants become smoothie-like, take them out, heat them to 20-22℃, and stir them for 5-10min to melt them into liquid. Send them to a 0-4℃ environment and let them stand for 12-14h for degassing to obtain the casting liquid.
[0021] Further, the volume ratio of the processed bamboo powder to the NaOH solution is 1:(8-12).
[0022] Furthermore, the volume ratio of the intermediate to the NaOH solution is 1:(15-20).
[0023] Furthermore, step S3 processes the glass substrate, including the following steps:
[0024] S3.1: Pour the casting solution evenly on the glass substrate and scrape it flat with a scraper, then immerse the glass substrate in a 5-8% dilute sulfuric acid solution for 20-30 minutes, take it out after the phase separation process is completed, rinse it with deionized water for 3 times, and then soak it in deionized water for 24-25 hours to obtain a glass substrate covered with a regenerated cellulose film;
[0025] S3.2: Place the glass substrate coated with the regenerated cellulose membrane facing down and immerse it in a 20wt% LiOH solution for 24-25 hours. After taking it out, rinse it twice with a 75wt% ethanol aqueous solution, then place it in a saturated LiCl solution for dialyzation for 24-26 hours, then take it out, rinse it three times with deionized water, and finally place it in a 50-55℃ oven to dry for 3-4 hours to obtain a glass substrate coated with a lithium-modified cellulose membrane.
[0026] Further, the concentration of the saturated LiCl solution is 19.6M.
[0027] Furthermore, the glass substrate covered with the lithium-modified cellulose film has a thickness of 20-30 nm.
[0028] A high-transmittance double-silver LOW-E glass is prepared by the above-mentioned preparation method of the high-transmittance double-silver LOW-E glass.
[0029] Compared with the prior art, the present invention has at least the following beneficial effects:
[0030] 1. The present invention treats a cellulose film with lithium hydroxide and then modifies the cellulose film with lithium chloride to obtain a glass substrate covered with a lithium-modified cellulose film. Lithium ions can combine with multiple hydroxyl groups through coordination bonds to form a cross-linked network structure, thereby enhancing the mechanical strength and thermal stability of the film. In addition, lithium modification does not significantly affect the transparency of cellulose. At the same time, the lithium-modified cellulose film has a certain bonding strength and hardness, which makes it difficult for the glass substrate to be broken due to external pressure and internal stress when receiving subsequent coating, thereby facilitating subsequent magnetron sputtering coating.
[0031] 2. The present invention utilizes peroxyformic acid to treat bamboo powder, and prepares a casting liquid by reacting the treated bamboo powder with urea and DMAC, and uses the casting liquid to coat a layer of cellulose film on a glass substrate. Utilizing bamboo powder to prepare the cellulose film can effectively utilize waste materials in the bamboo processing process and reduce resource waste. The bamboo cellulose film prepared from bamboo powder is a natural polymer material that can be degraded in the natural environment and will not cause pollution to the environment. At the same time, the treated bamboo cellulose film can maintain a high transparency and is suitable for use as a light-transmitting material. It also has a high tensile strength and good toughness that are unique to cellulose films, and prevents the glass substrate from breaking while ensuring light transmittance, thereby ensuring that the glass substrate is not easily damaged during subsequent magnetron sputtering coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.
[0033] Figure 1 The present invention is a flowchart of a method for preparing a high-transmittance double-silver Low-E glass used in an embodiment of the present invention. DETAILED DESCRIPTION
[0034] The following is a detailed description of a high-transmittance double-silver LOW-E glass and a preparation method thereof provided by the present invention in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.
[0035] Embodiment 1:
[0036] A method for preparing high-transmittance double-silver LOW-E glass, such as Figure 1 As shown, the following steps are included:
[0037] S1: Preparation and processing of bamboo powder
[0038] S1.1: Crush the raw bamboo stalks and pass them through an 80-mesh sieve, soak them in deionized water at a solid-liquid ratio of 1 g:10 mL, heat them to 80°C and soak them for 4 hours, then cool them to room temperature, add a peroxyformic acid solution, the peroxyformic acid solution is prepared by mixing 30% by mass hydrogen peroxide and 85% by mass formic acid in a volume ratio of 2:1, and the amount of peroxyformic acid added is 10 g peroxyformic acid per 1 g of crushed raw bamboo stalks, and then add 0.5% of the total mass of concentrated sulfuric acid in the system;
[0039] S1.2: Then, the mixture was heated to 80°C and reacted for 3 hours, and then centrifuged at a speed of 2000 r / min for 15 minutes, the liquid was removed by filtration, and the mixture was dried at 60°C for 3 hours to obtain the treated bamboo powder.
[0040] S2: Preparation of casting solution
[0041] S2.1: Soak the treated bamboo powder in a NaOH solution with a volume ratio of 1:8 between the treated bamboo powder and the NaOH solution, and heat to 60°C. After stirring for 3 hours, filter to remove the liquid, wash with deionized water for 3 times to obtain alkalized bamboo powder, mix the alkalized bamboo powder, urea and DMAC in a volume ratio of 1:3:2, heat to 80°C in an oil bath, and pass nitrogen at the same time, react for 1 hour, then stand and cool to room temperature, filter to remove the filtrate, then wash the filter residue with deionized water for 3 times, and dry in an oven at 50°C for 4 hours to obtain an intermediate;
[0042] S2.2: The intermediate is added to the NaOH solution, the volume ratio of the intermediate to the NaOH solution is 1:15, and the temperature is lowered to -20°C, and stirred at a speed of 60r / min for 3h. During the process, the reactant dissolves and gradually becomes transparent. The temperature of the reactant is detected during the cooling period until the temperature reaches -20°C. The reactant is taken out after it becomes a smoothie, heated to 20°C, and stirred for 5min to melt it into a liquid state, and sent to a 0°C environment for 12h for degassing to obtain a casting liquid;
[0043] S3: Treating the glass substrate
[0044] S3.1: Pour the casting solution evenly on the glass substrate and scrape it flat with a scraper, then immerse the glass substrate in a 5% dilute sulfuric acid solution for 20 minutes, take it out after the phase separation process is completed, rinse it with deionized water for 3 times, and then soak it in deionized water for 24 hours to obtain a glass substrate covered with a regenerated cellulose film;
[0045] S3.2: Place the glass substrate with the regenerated cellulose membrane coated side facing down and immerse it in a 20wt% LiOH solution for 24 hours. After taking it out, rinse it twice with a 75wt% ethanol aqueous solution, then put it into a saturated LiCl solution with a concentration of 19.6M for dialyzation for 24 hours, then take it out, rinse it three times with deionized water, and finally place it in a 50℃ oven to dry for 3 hours to obtain a glass substrate coated with a lithium-modified cellulose membrane. The thickness of the lithium-modified cellulose membrane is 20nm.
[0046] S4: Preparation of high-transmittance double-silver LOW-E glass
[0047] A film is coated on a glass substrate covered with a lithium-modified cellulose film by a magnetron sputtering coating process, wherein the film layer materials are, from bottom to top, the second film layer Si3N4 with a film thickness of 15 nm; the third film layer is ZnO with a film thickness of 12 nm; the fourth film layer is Ag with a thickness of 5 nm; the fifth film layer is Al2O3 with a film thickness of 20 nm; the sixth film layer is a lithium-modified cellulose film, the coating method is the same as step S3, and the thickness is 20 nm; the seventh film layer is Si3N4 with a film thickness of 15 nm; the eighth film layer is ZnO with a film thickness of 12 nm; the ninth film layer is Ag with a film thickness of 10 nm; the tenth film layer is Al2O3 with a film thickness of 20 nm; and the eleventh film layer is SnO2 with a thickness of 25 nm, thereby obtaining high-transmittance double-silver LOW-E glass.
[0048] Embodiment 2:
[0049] A method for preparing high-transmittance double-silver LOW-E glass, such as Figure 1 As shown, the following steps are included:
[0050] S1: Preparation and processing of bamboo powder
[0051] S1.1: Crush the raw bamboo stalks and pass them through an 80-mesh sieve, soak them in deionized water at a solid-liquid ratio of 1 g:15 mL, heat them to 80°C and soak them for 4 hours, then cool them to room temperature, add a peroxyformic acid solution, the peroxyformic acid solution is prepared by mixing 30% by mass hydrogen peroxide and 85% by mass formic acid in a volume ratio of 3:1, and the amount of peroxyformic acid added is 10 g peroxyformic acid per 1 g of crushed raw bamboo stalks, and then add 0.5% of the total mass of concentrated sulfuric acid in the system;
[0052] S1.2: Then, the mixture was heated to 80°C and reacted for 3 hours, and then centrifuged at a speed of 2000 r / min for 15 minutes, the liquid was removed by filtration, and the mixture was dried at 60°C for 3 hours to obtain the treated bamboo powder.
[0053] S2: Preparation of casting solution
[0054] S2.1: Soak the treated bamboo powder in a NaOH solution with a volume ratio of 1:12, and heat to 60°C. After stirring for 3 hours, filter to remove the liquid, wash with deionized water 3 times to obtain alkalized bamboo powder, mix the alkalized bamboo powder, urea and DMAC in a volume ratio of 1:3:4, heat to 80°C in an oil bath, and pass nitrogen at the same time, react for 1 hour, then stand and cool to room temperature, filter to remove the filtrate, then wash the filter residue with deionized water 3 times, and dry in an oven at 50°C for 4 hours to obtain an intermediate;
[0055] S2.2: The intermediate is added to the NaOH solution, the volume ratio of the intermediate to the NaOH solution is 1:20, and the temperature is lowered to -20°C, and stirred at a speed of 60r / min for 3h. During the process, the reactant dissolves and gradually becomes transparent. The temperature of the reactant is detected during the cooling period until the temperature reaches -20°C. The reactant is taken out after it becomes a smoothie, heated to 20°C, and stirred for 5min to melt it into a liquid state, and placed in a 0°C environment for 12h for degassing to obtain a casting liquid;
[0056] S3: Treating the glass substrate
[0057] S3.1: Pour the casting solution evenly on the glass substrate and scrape it flat with a scraper, then immerse the glass substrate in a 5% dilute sulfuric acid solution for 20 minutes, take it out after the phase separation process is completed, rinse it with deionized water for 3 times, and then soak it in deionized water for 24 hours to obtain a glass substrate covered with a regenerated cellulose film;
[0058] S3.2: Place the glass substrate with the regenerated cellulose membrane coated side facing down and immerse it in a 20wt% LiOH solution for 24 hours. After taking it out, rinse it twice with a 75wt% ethanol aqueous solution, then put it into a saturated LiCl solution with a concentration of 19.6M for dialyzation for 24 hours, then take it out, rinse it three times with deionized water, and finally place it in a 50℃ oven to dry for 3 hours to obtain a glass substrate coated with a lithium-modified cellulose membrane. The thickness of the lithium-modified cellulose membrane is 30nm.
[0059] S4: Preparation of high-transmittance double-silver LOW-E glass
[0060] A film is coated on a glass substrate covered with a lithium-modified cellulose film by a magnetron sputtering coating process, wherein the film layer materials are, from bottom to top, the second film layer Si3N4 with a film thickness of 20 nm; the third film layer is ZnO with a film thickness of 16 nm; the fourth film layer is Ag with a thickness of 8 nm; the fifth film layer is Al2O3 with a film thickness of 25 nm; the sixth film layer is a lithium-modified cellulose film, the coating method is the same as step S3, and the thickness is 30 nm; the seventh film layer is Si3N4 with a film thickness of 20 nm; the eighth film layer is ZnO with a film thickness of 16 nm; the ninth film layer is Ag with a film thickness of 15 nm; the tenth film layer is Al2O3 with a film thickness of 30 nm; and the eleventh film layer is SnO2 with a thickness of 35 nm, thereby obtaining high-transmittance double-silver LOW-E glass.
[0061] Embodiment 3:
[0062] A method for preparing high-transmittance double-silver LOW-E glass, such as Figure 1 As shown, the following steps are included:
[0063] S1: Preparation and processing of bamboo powder
[0064] S1.1: Crush the raw bamboo stalks and pass them through an 80-mesh sieve, soak them in deionized water at a solid-liquid ratio of 1 g:10 mL, heat them to 90°C and soak them for 6 hours, then cool them to room temperature, add a peroxyformic acid solution, the peroxyformic acid solution is prepared by mixing 30% by mass hydrogen peroxide and 85% by mass formic acid in a volume ratio of 2:1, and the amount of peroxyformic acid added is 10 g peroxyformic acid per 1 g of crushed raw bamboo stalks, and then add 0.5% of the total mass of concentrated sulfuric acid in the system;
[0065] S1.2: Then, heat to 100°C, react for 4 hours, centrifuge at 2200 r / min for 20 minutes, remove the liquid by suction filtration, and dry at 65°C for 4 hours to obtain treated bamboo powder.
[0066] S2: Preparation of casting solution
[0067] S2.1: Soak the treated bamboo powder in a NaOH solution with a volume ratio of 1:8 between the treated bamboo powder and the NaOH solution, and heat to 70°C. After stirring for 4 hours, filter to remove the liquid, wash with deionized water for 3 times to obtain alkalized bamboo powder, mix the alkalized bamboo powder, urea and DMAC in a volume ratio of 1:3:2, heat to 90°C in an oil bath, and pass nitrogen at the same time, react for 2 hours, then stand and cool to room temperature, filter to remove the filtrate, then wash the filter residue with deionized water for 3 times, and dry in an oven at 60°C for 5 hours to obtain an intermediate;
[0068] S2.2: The intermediate is added to the NaOH solution, the volume ratio of the intermediate to the NaOH solution is 1:15, and the temperature is lowered to -20°C, and stirred at a speed of 80r / min for 4h. During the process, the reactant dissolves and gradually becomes transparent. The temperature of the reactant is detected during the cooling period until the temperature reaches -20°C. The reactant is taken out after it becomes a smoothie, heated to 22°C, and stirred for 10min to melt it into a liquid state, and placed in a 4°C environment for 14h for degassing to obtain a casting liquid;
[0069] S3: Treating the glass substrate
[0070] S3.1: Pour the casting solution evenly on the glass substrate and scrape it flat with a scraper, then immerse the glass substrate in 8% dilute sulfuric acid solution for 30 minutes, take it out after the phase separation process is completed, rinse it with deionized water for 3 times, and then soak it in deionized water for 25 hours to obtain a glass substrate covered with a regenerated cellulose film;
[0071] S3.2: Place the glass substrate with the regenerated cellulose membrane coated side facing down and immerse it in a 20wt% LiOH solution for 25 hours. After taking it out, rinse it twice with a 75wt% ethanol aqueous solution, then put it into a saturated LiCl solution with a concentration of 19.6M for dialyzation for 26 hours. Then take it out, rinse it three times with deionized water, and finally dry it in a 55℃ oven for 4 hours to obtain a glass substrate coated with a lithium-modified cellulose membrane. The thickness of the lithium-modified cellulose membrane is 20nm.
[0072] S4: Preparation of high-transmittance double-silver LOW-E glass
[0073] A film is coated on a glass substrate covered with a lithium-modified cellulose film by a magnetron sputtering coating process, wherein the film layer materials are, from bottom to top, the second film layer Si3N4 with a film thickness of 15 nm; the third film layer is ZnO with a film thickness of 12 nm; the fourth film layer is Ag with a thickness of 5 nm; the fifth film layer is Al2O3 with a film thickness of 20 nm; the sixth film layer is a lithium-modified cellulose film, the coating method is the same as step S3, and the thickness is 20 nm; the seventh film layer is Si3N4 with a film thickness of 15 nm; the eighth film layer is ZnO with a film thickness of 12 nm; the ninth film layer is Ag with a film thickness of 10 nm; the tenth film layer is Al2O3 with a film thickness of 20 nm; and the eleventh film layer is SnO2 with a thickness of 25 nm, thereby obtaining high-transmittance double-silver LOW-E glass.
[0074] Comparative Example 1:
[0075] Compared with Example 1, Comparative Example 1 is commercially available double-silver LOW-E glass.
[0076] Comparative Example 2:
[0077] Compared with Example 1, the difference of Comparative Example 2 is that step S3.2 is not performed, and the glass substrate covered with the lithium-modified cellulose film in step S4 is replaced with a glass substrate covered with a regenerated cellulose film, specifically: "S4: Preparation of high-transmittance double-silver LOW-E glass
[0078] A film is coated on a glass substrate covered with a regenerated cellulose film by a magnetron sputtering coating process, wherein the film layer materials are, from bottom to top, the second film layer Si3N4, with a film thickness of 15 nm; the third film layer is ZnO, with a film thickness of 12 nm; the fourth film layer is Ag, with a thickness of 5 nm; the fifth film layer is Al2O3, with a film thickness of 20 nm; the sixth film layer is a regenerated cellulose film, the coating method is as in step S3.1, and the thickness is 20 nm; the seventh film layer is Si3N4, with a film thickness of 15 nm; the eighth film layer is ZnO, with a film thickness of 12 nm; the ninth film layer is Ag, with a film thickness of 10 nm; the tenth film layer is Al2O3, with a film thickness of 20 nm; and the eleventh film layer is SnO2, with a thickness of 25 nm, to obtain a "high transmittance double silver LOW-E glass", and the prepared high transmittance double silver LOW-E glass is recorded as Comparative Example 2.
[0079] Comparative Example 3:
[0080] Compared with Example 1, the difference of Comparative Example 3 is that, instead of adding treated bamboo powder, wood cellulose is added in step S2.1, specifically: "S2.1: soaking the wood cellulose in a NaOH solution, the volume ratio of the wood cellulose to the NaOH solution is 1:8, and heating to 60°C, stirring for 3 hours, filtering to remove the liquid, washing with deionized water 3 times to obtain alkalized wood cellulose, mixing the alkalized wood cellulose, urea and DMAC in a volume ratio of 1:3:2, heating to 80°C in an oil bath, and passing nitrogen at the same time, reacting for 1 hour, then standing and cooling to room temperature, filtering to remove the filtrate, then washing the filter residue with deionized water 3 times, and drying in a 50°C oven for 4 hours to obtain an intermediate", and the prepared high-transmittance double-silver LOW-E glass is recorded as Comparative Example 3.
[0081] The visible light transmittance, outdoor visible light reflectance and indoor visible light reflectance of Examples 1-3 and Comparative Examples 1-3 were tested according to NFRC100-2004 standard, as shown in Table 1.
[0082] Table 1 (Unit: %)
[0083]
[0084] The visible light transmittance of Examples 1-3 is above 51.3%, which is higher than that of the comparative example. It can be seen that the high-transmittance double-silver LOW-E glass of the present application has good transmittance, and the indoor and outdoor visible light reflectance of Examples 1-3 is lower than that of the comparative example, indicating that the examples have better anti-reflection effect and can reduce the reflected light on the glass surface.
[0085] The visible light transmittance of Comparative Example 1 is 50.2%, the outdoor visible light reflectance is 13.2%, and the indoor visible light reflectance is 10.1%. It can be seen that the light transmittance of the commercially available product is not as high as that of the present invention, and the anti-reflection effect is also weaker.
[0086] The visible light transmittance of Comparative Example 2 is 48.8%, the outdoor visible light reflectance is 14.7%, and the indoor visible light reflectance is 12.4%. The visible light transmittance of Comparative Example 3 is 49.2%, the outdoor visible light reflectance is 15.2%, and the indoor visible light reflectance is 13.1%, indicating that lithium modification and the use of bamboo powder as a cellulose source both affect the transmittance, and lithium modification has a greater effect on the transmittance of the cellulose film, while bamboo powder as a cellulose source has a greater effect on the light reflectance of the cellulose film.
[0087] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing high-transmittance double-silver LOW-E glass, characterized in that: The steps include: S1: Preparation and processing of bamboo powder The raw bamboo stalks are crushed and sieved, soaked in deionized water, heated, then allowed to stand and cool to room temperature, peroxyformic acid solution is added, and then concentrated sulfuric acid is added, followed by heating for 3-4 hours, centrifuged, filtered to remove the liquid, and dried to obtain treated bamboo powder; S2: Preparation of casting solution The treated bamboo powder is immersed in a NaOH solution, and the liquid is filtered out after heating and stirring, and the powder is washed with deionized water three times to obtain an alkalized bamboo powder, the alkalized bamboo powder, urea and DMAC are mixed, and the mixture is heated in an oil bath for reaction, and then the mixture is allowed to stand and cool to room temperature, the filtrate is filtered out, the filter residue is washed and dried to obtain an intermediate, the intermediate is added to a NaOH solution, and the mixture is taken out after cooling and stirring, and the mixture is heated, and the mixture is allowed to stand and degassed to obtain a casting solution; S3: Treating the glass substrate The casting liquid is evenly poured on the glass substrate and scraped flat with a scraper, and then the glass substrate is immersed in a dilute sulfuric acid solution, taken out after the phase separation process is completed, and rinsed with deionized water to obtain a glass substrate covered with a regenerated cellulose membrane, and the glass substrate with the regenerated cellulose membrane is immersed in a LiOH solution with the membrane-covered side facing downward, taken out and rinsed, and then dialyzed in a saturated LiCl solution, taken out and rinsed, and dried to obtain a glass substrate covered with a lithium-modified cellulose membrane; S4: Preparation of high-transmittance double-silver Low-E glass A film is coated on a glass substrate covered with a lithium-modified cellulose film by a magnetron sputtering coating process, wherein the film layer materials are, from bottom to top, the second film layer Si3N4, with a film thickness of 15-20nm; the third film layer is ZnO, with a film thickness of 12-16nm; the fourth film layer is Ag, with a thickness of 5-8nm; the fifth film layer is Al2O3, with a film thickness of 20-25nm; the sixth film layer is a lithium-modified cellulose film, the coating method is the same as step S3, with a thickness of 20-30nm; the seventh film layer is Si3N4, with a film thickness of 15-20nm; the eighth film layer is ZnO, with a film thickness of 12-16nm; the ninth film layer is Ag, with a film thickness of 10-15nm; the tenth film layer is Al2O3, with a film thickness of 20-30nm; and the eleventh film layer is SnO2, with a thickness of 25-35nm, thereby obtaining high-transmittance double-silver LOW-E glass.
2. The method for preparing high-transmittance double-silver LOW-E glass according to claim 1, characterized in that: Step S1: preparing and treating bamboo powder, comprising the following steps: S1.1: Crush the raw bamboo stems and pass them through an 80-mesh sieve, soak them in deionized water at a solid-liquid ratio of 1 g: (10-15) mL, heat them to 80-90°C and soak them for 4-6 hours, then cool them to room temperature, add a peroxyformic acid solution, and add 10 g of peroxyformic acid per 1 g of crushed raw bamboo stems, and then add concentrated sulfuric acid at a total mass of 0.5% of the system; S1.2: Then heat to 80-100°C, react for 3-4h, then centrifuge at 2000-2200r / min for 15-20min, remove the liquid by suction filtration, and dry at 60-65°C for 3-4h to obtain treated bamboo powder.
3. The method for preparing high-transmittance double-silver LOW-E glass according to claim 2, characterized in that: The peroxyformic acid solution is prepared by mixing 30% by mass of hydrogen peroxide and 85% by mass of formic acid in a volume ratio of (2-3):
1.
4. The method for preparing high-transmittance double-silver LOW-E glass according to claim 2, characterized in that: Step S2 is preparing a casting solution, comprising the following steps: S2.1: Soak the treated bamboo powder in a NaOH solution and heat it to 60-70°C. After stirring for 3-4 hours, filter and remove the liquid, wash with deionized water for 3 times to obtain alkalized bamboo powder, mix the alkalized bamboo powder, urea and DMAC in a volume ratio of 1:3:(2-4), heat to 80-90°C in an oil bath, and pass nitrogen at the same time, react for 1-2 hours, then stand and cool to room temperature, filter and remove the filtrate, then wash the filter residue with deionized water for 3 times, and dry it in an oven at 50-60°C for 4-5 hours to obtain an intermediate; S2.2: Add the intermediate into NaOH solution, cool it to -20℃, and stir it at 60-80r / min for 3-4h. During the process, the reactants dissolve and gradually become transparent. During the cooling period, check the temperature of the reactants until the temperature reaches -20℃. After the reactants become smoothie-like, take them out, heat them to 20-22℃, and stir them for 5-10min to melt them into liquid. Send them to a 0-4℃ environment and let them stand for 12-14h for degassing to obtain the casting liquid.
5. The method for preparing high-transmittance double-silver LOW-E glass according to claim 4, characterized in that: The volume ratio of processed bamboo powder to NaOH solution is 1:(8-12).
6. The method for preparing high-transmittance double-silver LOW-E glass according to claim 4, characterized in that: The volume ratio of the intermediate to the NaOH solution is 1:(15-20).
7. The method for preparing high-transmittance double-silver LOW-E glass according to claim 4, characterized in that: Step S3 processes the glass substrate, including the following steps: S3.1: Pour the casting solution evenly on the glass substrate and scrape it flat with a scraper, then immerse the glass substrate in a 5-8% dilute sulfuric acid solution for 20-30 minutes, take it out after the phase separation process is completed, rinse it with deionized water for 3 times, and then soak it in deionized water for 24-25 hours to obtain a glass substrate covered with a regenerated cellulose film; S3.2: Place the glass substrate coated with the regenerated cellulose membrane facing down and immerse it in a 20wt% LiOH solution for 24-25 hours. After taking it out, rinse it twice with a 75wt% ethanol aqueous solution, then place it in a saturated LiCl solution for dialyzation for 24-26 hours, then take it out, rinse it three times with deionized water, and finally place it in a 50-55℃ oven to dry for 3-4 hours to obtain a glass substrate coated with a lithium-modified cellulose membrane.
8. The method for preparing high-transmittance double-silver LOW-E glass according to claim 7, characterized in that: The concentration of saturated LiCl solution is 19.6M.
9. The method for preparing high-transmittance double-silver LOW-E glass according to claim 1, characterized in that: The glass substrate is coated with a lithium-modified cellulose film, wherein the thickness of the lithium-modified cellulose film is 20-30 nm.
10. A high-transmittance double-silver LOW-E glass, prepared by the preparation method of the high-transmittance double-silver LOW-E glass according to any one of claims 1 to 9.